Global solar radiation over Turkey: comparison of predicted and measured data - Togrul, IT; Togrul, H (Pergamon-Elsevier Science Ltd, 2002)
In this study, various regression analyses were applied to estimate monthly mean solar radiation in Turkey, by using (n) over bar/(N) over bar and (n) over bar/(N) over bar (nh) parameters. Also, equations which represent two periods of the year, winter and summer, were developed by using these parameters. The equations developed by using (n) over bar/(N) over bar (nh) ratio showed good results for the whole country, but, those which included (n) over bar/(N) over bar ratio at different cities showed better results. Even better results were obtained when the equations were applied to the summer and winter. In addition to RMSE and MBE statistics, the t-test method and the harmonic analysis were employed to prove that the results are reliable. (C) 2001 Elsevier Science Ltd. All rights reserved.
Keywords: estimation of solar radiation; t-statistic